Copper Electropolishing in the Presence of Purine Derivatives - Ahmed, A.M.; Abd El-Haleem, S.M.; Saleh, M.G.A.; Abdel-Rahman, A.A.-H. (Asian Journal of Chemistry, 2012)
The electropolishing settings for inhibiting the rate of anodic corrosion of copper plates in phosphoric acid were achieved using potentiodynamic studies including different factors such as plate height, phosphoric acid concentration, type and concentration of purines as well as temperature. The results reveal that purines have strongest inhibitive effect ranging from 9.7 to 80.1 % that provides good protection to copper surface against corrosion in phosphoric acid solutions. Its adsorption obeys Langmuir, Flory-Huggins and kinetic adsorption isotherm. Thermodynamic functions computed and discussed.